THE ROLE OF DIGITAL TECHNOLOGY IN INCREASING THE COMPETITIVENESS OF MSMES IN INDONESIA: A DEVELOPMENT ECONOMY PERSPECTIVE - Nur Ihsan, Hamidi; Aisya, Hanifa; Isnanto, Dedi (Jurnal Multidisipliner Bharasa, 2024)
This study examines the role of digital technology in increasing the competitiveness of micro, small, and medium enterprises (MSMEs) in Indonesia from the perspective of development economics. MSMEs play a vital role in Indonesia's economy, but often face challenges in competing in the global market. Digital technologies, including e-commerce, fintech, and social media platforms, are identified as strategic tools that can improve operational efficiency, expand market access, and drive innovation in the MSME sector. This research uses qualitative and quantitative approaches, with data obtained through in-depth surveys and interviews with MSME owners in various industry sectors. The analysis shows that the adoption of digital technology significantly increases the competitiveness of MSMEs, especially in terms of access to a wider market, more efficient financial management, and the ability to innovate. However, this study also found significant obstacles, such as a lack of digital literacy and limited infrastructure, which hinder the optimization of the benefits of digital technology for MSMEs. Therefore, policy interventions are needed that support the improvement of digital literacy and the strengthening of infrastructure, so that digital technology can be accessed equally by MSMEs throughout Indonesia.